Learning to Speak, Learning to Listen : How Diversity Works on Campus - Chase, Susan E., 1954- (Book collections on Project MUSE., 2010)
Over the past three decades, colleges and universities have committed to encouraging, embracing, and supporting diversity as a core principle of their mission. But how are goals for achieving and maintaining diversity actually met? What is the role of students in this mission? When a university is committed to diversity, what is campus culture like?In Learning to Speak, Learning to Listen, Susan E. Chase portrays how undergraduates at a predominantly white urban institution, which she calls "City University" (a pseudonym), learn to speak and listen to each other across social differences. Chase interviewed a wide range of students and conducted content analyses of the student newspaper, student government minutes, curricula, and website to document diversity debates at this university. Amid various controversies, she identifies a defining moment in the campus culture: a protest organized by students of color to highlight the university's failure to live up to its diversity commitments. Some white students dismissed the protest, some were hostile to it, and some fully engaged their peers of color.In a book that will be useful to students and educators on campuses undergoing diversity initiatives, Chase finds that both students' willingness to share personal stories about their diverse experiences and collaboration among student organizations, student affairs offices, and academic programs encourage speaking and listening across differences and help incorporate diversity as part of the overall mission of the university.